The local South African worshipping community as a site for spiritual formation towards transformation - Meylahn, Johann-Albrecht (Verbum et ecclesia, 2014)
The article focuses on the local worshipping community as a site for the spiritual formation ofcitizens to become agents of transformation in public life. How are citizens spiritually formedso that, through their witness and praxis, they become instruments of transformation, therebychallenging the dominant discourses by offering, through their collective witness and praxis,redeeming alternatives? To answer this question, the article focuses not on a methodology butrather offers suggestions as to how to nurture a radical spirituality towards the formation ofagents of transformation. The specific South African context with its numerous socioeconomicand political challenges as well as the plurality of voices and values need to be taken intoconsideration. Therefore the challenge is to develop an inclusive spirituality.